2013
DOI: 10.3389/fncel.2013.00073
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal depression and maternal selective serotonin reuptake inhibitor exposure on offspring

Abstract: It has been estimated that 20% of pregnant women suffer from depression and it is well-documented that maternal depression can have long-lasting effects on the child. Currently, common treatment for maternal depression has been the selective serotonin reuptake inhibitor medications (SSRIs) which are used by 2–3% of pregnant women in the Nordic countries and by up to 10% of pregnant women in the United States. Antidepressants cross the placenta and are transferred to the fetus, thus, the question arises as to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 179 publications
(304 reference statements)
3
67
1
Order By: Relevance
“…The biologic plausibility of a teratogenic effect of SSRIs in humans is based on studies of drug and metabolite levels in amniotic fluid and cord blood combined with evidence from animal studies [52]. Most SSRIs have a short half-life (approximately 1 day).…”
Section: Ssri Use In First Trimester Pregnancy and Risk Of Congenitalmentioning
confidence: 99%
“…The biologic plausibility of a teratogenic effect of SSRIs in humans is based on studies of drug and metabolite levels in amniotic fluid and cord blood combined with evidence from animal studies [52]. Most SSRIs have a short half-life (approximately 1 day).…”
Section: Ssri Use In First Trimester Pregnancy and Risk Of Congenitalmentioning
confidence: 99%
“…Antenatal depression is an established cause of child emotional and behavioral problems (21). Low LC-PUFA status might place women at risk of depression or can result from dietary changes due to depression (22).…”
Section: Mechanism Of Riskmentioning
confidence: 99%
“…Extensive studies in animal models have demonstrated the important role of serotonin in foetal neurodevelopment (Velasquez et al 2013). Studies in pregnant women diagnosed with mood disorders, or receiving treatment with selective serotonin reuptake inhibitors (SSRIs), are also consistent with a key role for serotonin pathways in foetal development (Oberlander 2012;Olivier et al 2013), with effects persisting at least to childhood. The serotonin and glucocorticoid signalling systems also interact, with glucocorticoids regulating serotonin synthesis, transport, re-uptake and neuronal receptor expression, whilst serotonin controls glucocorticoid and mineralocorticoid receptor expression in the central nervous system (Wyrwoll and Holmes 2012).…”
Section: Changes In Placental Growth Gene Expression and Epigenetic mentioning
confidence: 96%